Effective wake estimation of KCS hull at full-scale by GEOSIM method based on CFD - Can, Ugur; Delen, Cihad; Bal, Sakir (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, the effective wake factors of a self-propelled container ship were investigated by Telfer's GEOSIM method based on CFD (Computational Fluid Dynamics). For this purpose, the self-propulsion characteristics of KCS (KRISO Container Ship) at three different model scales and full-scale were determined at Fr = 0.26 by unsteady RANS (Reynolds Averaged Navier-Stokes) solver. All scales corresponded to a wide range of Reynolds numbers. Turbulent flow around the KCS hull has been investigated by the k-e turbulence model. Heave and pitch motions of KCS hulls have been modeled with the DFBI (Dynamic Fluid Body Interaction) method and overset mesh technique. The rotational motion of KP505 propeller has been simulated using the RBM (Rigid Body Motion) approach. The result obtained by the extrapolation of the effective wake fraction with the GEOSIM method was compared with the full-scale ones of CFD and ITTC methods. The results by the GEOSIM method are more compatible with those of full-scale CFD than the results of 1978 ITTC method. In the wake region, where viscous effects are predominant, the change of effective wake fraction with Reynolds number has been successfully represented by the GEOSIM method, thus more robust and reliable results have been found.
Keywords: GEOSIM series; Effective wake fraction; Self-propulsion; Full-scale KCS; Rigid body motion; Scale effect; SHIP; RANS; PROPELLER; MODEL; Engineering; Oceanography